Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) ĐKXĐ: \(x\notin\left\{\frac{1}{3};\frac{-11}{3}\right\}\)
Ta có: \(\frac{2}{\left(1-3x\right)\left(3x+11\right)}=\frac{1}{9x^2-6x+1}-\frac{3}{\left(3x+11\right)^2}\)
\(\Leftrightarrow\frac{2\left(1-3x\right)\left(3x+11\right)}{\left(1-3x\right)^2\cdot\left(3x+11\right)^2}=\frac{\left(3x+11\right)^2}{\left(1-3x\right)^2\cdot\left(3x+11\right)^2}-\frac{3\left(1-3x\right)^2}{\left(1-3x\right)^2\cdot\left(3x+11\right)^2}\)
\(\Leftrightarrow-18x^2-60x+22=9x^2+66x+121-3\left(1-6x+9x^2\right)\)
\(\Leftrightarrow-18x^2-60x+22-9x^2-66x-121+3\left(1-6x+9x^2\right)=0\)
\(\Leftrightarrow-27x^2-126x-99+3-18x+27x^2=0\)
\(\Leftrightarrow-144x-96=0\)
\(\Leftrightarrow-144x=96\)
hay \(x=\frac{-2}{3}\)(tm)
Vậy: \(x=\frac{-2}{3}\)
a) <=> \(6x^2-5x+3-2x+3x\left(3-2x\right)=0\)
<=> \(6x^2-5x+3-2x+9x-6x^2=0\)
<=> \(2x+3=0\)
<=> \(x=\frac{-3}{2}\)
b) <=> \(10\left(x-4\right)-2\left(3+2x\right)=20x+4\left(1-x\right)\)
<=> \(10x-40-6-4x=20x+4-4x\)
<=> \(6x-46-16x-4=0\)
<=> \(-10x-50=0\)
<=> \(-10\left(x+5\right)=0\)
<=> \(x+5=0\)
<=> \(x=-5\)
c) <=> \(8x+3\left(3x-5\right)=18\left(2x-1\right)-14\)
<=> \(8x+9x-15=36x-18-14\)
<=> \(8x+9x-36x=+15-18-14\)
<=> \(-19x=-14\)
<=> \(x=\frac{14}{19}\)
d) <=>\(2\left(6x+5\right)-10x-3=8x+2\left(2x+1\right)\)
<=> \(12x+10-10x-3=8x+4x+2\)
<=> \(2x-7=12x+2\)
<=> \(2x-12x=7+2\)
<=> \(-10x=9\)
<=> \(x=\frac{-9}{10}\)
e) <=> \(x^2-16-6x+4=\left(x-4\right)^2\)
<=> \(x^2-6x-12-\left(x-4^2\right)=0\)
<=> \(x^2-6x-12-\left(x^2-8x+16\right)=0\)
<=> \(x^2-6x-12-x^2+8x-16=0\)
<=> \(2x-28=0\)
<=> \(2\left(x-14\right)=0\)
<=> x-14=0
<=> x=14
c) ĐK: $x\neq \pm 2$
PT \(\Leftrightarrow \frac{x-2}{x+2}-\frac{3}{x-2}=\frac{2(x-11)}{x^2-4}\)
\(\Leftrightarrow \frac{(x-2)^2-3(x+2)}{(x+2)(x-2)}=\frac{2(x-11)}{(x-2)(x+2)}\)
\(\Leftrightarrow \frac{x^2-7x-2}{(x-2)(x+2)}=\frac{2x-22}{(x-2)(x+2)}\)
\(\Rightarrow x^2-7x-2=2x-22\)
\(\Leftrightarrow x^2-9x+20=0\Leftrightarrow (x-4)(x-5)=0\Rightarrow x=4\) hoặc $x=5$
(đều thỏa mãn)
d) ĐK: \(x^2-6x+7\neq 0\)
PT \(\Leftrightarrow (x^2-6x+7)+\frac{14}{x^2-6x+7}-9=0\)
\(\Rightarrow (x^2-6x+7)^2-9(x^2-6x+7)+14=0\)
\(\Leftrightarrow (x^2-6x+7-2)(x^2-6x+7-7)=0\)
\(\Leftrightarrow (x^2-6x+5)(x^2-6x)=0\)
\(\Leftrightarrow (x-1)(x-5)x(x-6)=0\)
\(\Rightarrow x\in \left\{1;5;0;6\right\}\) (đều thỏa mãn)
Vậy.........
a) ĐKXĐ: $x\neq 1$
PT \(\Leftrightarrow \frac{x^2+x+1+2(x-1)}{(x-1)(x^2+x+1)}=\frac{3x^2}{x^3-1}\)
\(\Leftrightarrow \frac{x^2+3x-1}{x^3-1}=\frac{3x^2}{x^3-1}\)
\(\Rightarrow x^2+3x-1=3x^2\Leftrightarrow 2x^2-3x+1=0\)
\(\Leftrightarrow (x-1)(2x-1)=0\)
Mà $x\neq 1$ nên $2x-1=0\Rightarrow x=\frac{1}{2}$ là nghiệm
b) ĐK: $x\neq \pm 2$
PT \(\Leftrightarrow \frac{3-x}{2-x}=\frac{1}{x+2}-\frac{6-x}{3x^2-12}\)
\(\Leftrightarrow \frac{1}{x+2}-\frac{3-x}{2-x}=\frac{6-x}{3(x^2-4)}\)
\(\Leftrightarrow \frac{1}{x+2}+\frac{3-x}{x-2}=\frac{6-x}{3(x-2)(x+2)}\)
\(\Leftrightarrow \frac{-x^2+2x+4}{(x-2)(x+2)}=\frac{6-x}{3(x-2)(x+2)}\)
\(\Rightarrow 3(-x^2+2x+4)=6-x\)
\(\Leftrightarrow -3x^2+7x+6=0\)
\(\Leftrightarrow (x-3)(3x+2)=0\Rightarrow x=3\) hoặc $x=-\frac{2}{3}$
Vậy........